The effect of Instructional Program about Diagnostic and Therapeutic Intervention for Infertility upon Infertile Women’s Knowledge in Kamal Al-Samaraee Hospital - Ghafel, hawraa; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To determine the effect of instructional program on infertile women's knowledge regardingdiagnostic and therapeutic intervention for infertility.Methodology: Non-probability (purposive sample) of (100) infertile women, who visit Kamal Al-Samaraee Hospital/fertility and IVF center. The data are collected through the use of constructed questionnaire, which included:demographic characteristics, social status, previous medical history, reproductive status, sexual status and questionsregarding women’s knowledge about infertility. Instrument validity and reliability was determined. Data werecollected through the use of questionnaire, the application of the instructional program was done for the study groupwhich use the lectures, booklets and video film. Analysis of data was performed through the application of descriptiveand inferential statistical data analysis approach.Results : Revealed that the infertile women in the study group had benefited from the implementation of theinstructional program ; their knowledge was adequately improved and developed. The study illustrated significantdifference between women's knowledge means in pre and post periods.Recommendations: the study recommended that all the fertility centers in Iraq should be includesinstructional programs about diagnostic and therapeutic intervention for infertility